Review: The conservation of Tengger indigenous people's traditional knowledge of biological natural resource?based disease treatments - EMILDA KUSPRANINGRUM; THOHIR LUTH; YULIATI YULIATI; RACHMAD SAFA’AT; Harlinda Kuspradini (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kuspraningrum E, Luth T, Yuliati, Safa'at R, Kuspradini H. 2020. Review: The conservation of Tengger indigenous people's traditional knowledge of biological natural resource?based disease treatments. Biodiversitas 21: 5040-5053. The indigenous people of Tengger, a community living around Bromo Mountain in East Java, frequently use ethnic knowledge to process biological natural resources into medicines used to cure diseases. These include Foeniculum vulgare Mill. tree, Tithonia diversifolia/insulin tree, Mikania cordata L. and Bidens pilosa tree, Cyphomandra betacea (Cav.) Sendtn., and Acorus calamus L. This intelligence is acquired consciously to solve health problems. In addition, the bond between the community and nature is highly philosophical, hence the presence of respect and maintaining the harmony of Knowledge obtained from nature ensures life continuity. Therefore, the belief is passed on through the generations, and traditional knowledge is attained following the gain of existence. This phenomenon is proven by numerous modern researches with scientific methods that admit the plant healing properties. In addition, traditional knowledge is a significant topic of interest in the United Nations' Convention on Biological Diversity, and was thus ratified by Law Number 5 of 1994. The object of this research is potential medicinal plants for healing and tengger indigenous people’s conservation model is to provide a platform to protect the interest of biological resources, including their use in the field of medicines belonging to indigenous peoples. Therefore, the empirical interdisciplinary research involves the compilation of data from the collection of similar scientific journals, for use as evidence. This is important to ascertain the existence of traditional medicine based on natural resources, followed by integrations with other disciplines, including the laws to be developed concerning the best protection methods. Furthermore, this investigation is essential for identifying the philosophical values of Tengger people, the importance of knowledge conservation, and recognizing the laws and regulations-based efforts aimed at protecting information on plant-based medicine production from extinction and biopiracy. These considerations are important because the absence of government intervention, alongside the preservation of plant species and traditional knowledge on treatment predisposes the possibility of destruction.